2019
DOI: 10.1111/bju.14759
|View full text |Cite
|
Sign up to set email alerts
|

Biparametric vs multiparametric prostate magnetic resonance imaging for the detection of prostate cancer in treatment‐naïve patients: a diagnostic test accuracy systematic review and meta‐analysis

Abstract: Objective To perform a diagnostic test accuracy (DTA) systematic review and meta‐analysis comparing multiparametric (diffusion‐weighted imaging [DWI], T2‐weighted imaging [T2WI], and dynamic contrast‐enhanced [DCE] imaging) magnetic resonance imaging (mpMRI) and biparametric (DWI and T2WI) MRI (bpMRI) in detecting prostate cancer in treatment‐naïve patients. Methods The Medical Literature Analysis and Retrieval System Online (MEDLINE) and Excerpta Medica dataBASE (EMBASE) were searched to identify relevant stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
74
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 68 publications
4
74
1
1
Order By: Relevance
“…This approach is supported by recent systematic reviews and meta-analyses comparing standard mpMRI with biparametric MRI (bpMRI), the latter consisting of T2W and DWI sequences without DCE. In a meta-analysis by Alabousi et al [8] the pooled summary statistics had no significant difference in sensitivity (mpMRI: 86%, 95% CI 81-90; bpMRI: 90%, 95% CI 83-94) or specificity (mpMRI: 73%, 95% CI 64-81; bpMRI: 70%, 95% CI 42-83) with the summary AUROC values being comparable for mpMRI (0.87) and bpMRI (0.90) [8]. Subsequent to this, van der Leest et al [10] showed that sensitivity for high-grade prostate cancer of both bpMRI and mpMRI was 95% (95% CI 91-97), with a specificity of 69% (95% CI 64-73).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is supported by recent systematic reviews and meta-analyses comparing standard mpMRI with biparametric MRI (bpMRI), the latter consisting of T2W and DWI sequences without DCE. In a meta-analysis by Alabousi et al [8] the pooled summary statistics had no significant difference in sensitivity (mpMRI: 86%, 95% CI 81-90; bpMRI: 90%, 95% CI 83-94) or specificity (mpMRI: 73%, 95% CI 64-81; bpMRI: 70%, 95% CI 42-83) with the summary AUROC values being comparable for mpMRI (0.87) and bpMRI (0.90) [8]. Subsequent to this, van der Leest et al [10] showed that sensitivity for high-grade prostate cancer of both bpMRI and mpMRI was 95% (95% CI 91-97), with a specificity of 69% (95% CI 64-73).…”
Section: Discussionmentioning
confidence: 99%
“…It also recommends dominant sequences based on zonal anatomy so that DWI is dominant in the peripheral zone and T2W is dominant in the transition zone. Recent systematic reviews have indicated that DCE may not be necessary [8,9]; this is supported by results from paired-cohort studies from expert centres [10,11].…”
Section: Introductionmentioning
confidence: 87%
“…The identification of significant prostate cancer (PCa) has been limited by the absence of a dependable screening test able to accurately detect and localize the tumour . Case identification combines clinical features including family history, clinical assessment (digital rectal examination (DRE)) together with laboratory tests (prostate‐specific antigen (PSA)) . Ultrasound guided prostate biopsy is currently the gold standard in PCa diagnosis, but large‐scale international studies report a wide range of positive biopsy rates, anywhere from 24% to 48% .…”
Section: Introductionmentioning
confidence: 99%
“…1 Case identification combines clinical features including family history, clinical assessment (digital rectal examination (DRE)) together with laboratory tests (prostate-specific antigen (PSA)). 2 Ultrasound guided prostate biopsy is currently the gold standard in PCa diagnosis, but largescale international studies report a wide range of positive biopsy rates, anywhere from 24% to 48%. 3,4 A significant challenge in the diagnosis of PCa is that it remains one of the few cancers to be diagnosed with non-targeted tissue sampling.…”
Section: Introductionmentioning
confidence: 99%
“…The systematic review in this issue of the BJUI by Alabousi et al. explores, via the process of systematic review, whether the omission of the T1‐GAD sequence results in any clinically important reduction in test performance when compared with the full sequence scan comprising traditionally of T2, diffusion, and T1‐GAD sequences. It did not.…”
mentioning
confidence: 99%